PHYSICOCHEMICAL ANALYSIS AND CHARACTERIZATION OF BIODIESEL PRODUCTION FROM RICINUS COMMUNIS SEED OIL - Mustapha, L. M.; Shago, M. I.; Burhanudden, R. H.; Suleiman, G. (FUDMA Journal of Sciences, 2021)
The global energy concern with the availability of recoverable fossil fuel reserves and the environmental problems caused by those fossil fuels, considerable attention has been given to biodiesel production as an alternative to petro diesel worldwide. In this research, the seed oil of Ricinus communis (castor bean) was investigated for its viability as a feedstock for biodiesel production. The oil was extracted from the seed using petroleum ether .The oil quality characteristics of the seed oil were; Acid values for both Ricinus communis oil and biodiesel, 4.208 and3.93, and free fatty acids for both Ricinus communis and biodiesel were 1.2408 and 2.508, saponification value (SV) for both Ricinus communis and biodiesel, 185.0 and 173.16, specific gravity (S.G) for both Ricinus communis and biodiesel, 0.976g/ml and 0.935g/ml. the PH value for both Ricinus communis and biodiesel, 6.67 and 6.8. Refractive index for both Ricinus communis and biodiesel, 1.37 and 1.191, moisture content of seed, 0.052. Colour for both and Ricinus communis oil and biodiesel is brown colour and amber colour, respectively. The oil was transesterified using methanol and concentrated sulphuric acid. And with other investigated oils from the literature and were found to fall within acceptable limits, this implies that Ricinus communis seed oil could be used as diesel in combustion engines in tropical climates like Nigeria.